Does the quality of industrial relations matter for the macro economy? A cross-country analysis using strikes data - John T. Addison; Paulino Teixeira (Institute for the Study of Labor (IZA), 2006)
Using international data, we investigate whether the quality of industrial relations matters for the macro economy. We measure industrial relations inversely by strikes - which proxy we cross-check with an industrial relations reputation indicator - and our macro performance outcome is the unemployment rate. Independent of the role of other institutions, good industrial relations do seem to matter: greater strike volume is associated with higher unemployment. Holding country effects constant, however, the sign of the variable is reversed. This fixed-effects result likely picks up a direct effect of strikes, namely, their tendency to rise when striking becomes more attractive to the union.
Keywords: E24; J52; J53; J64; J65; 330; strike rate/volume; quality of labor relations; labor market institutions; unemployment